Lower extremity strength and recovery time in youth baseball pitchers: A pilot study - Livingston, J. L.; Tavoukjian, N. M. (The Journal of Strength and Conditioning Research, 2020)
The purpose of this study was to investigate the Little League pitching regulations by measuring the change in lower extremity force production after a pitching performance and the subsequent days of rest required for youth baseball pitchers to recover. Bilateral manual muscle testing of the gluteus maximus, hamstrings, gluteus medius, triceps surae, and quadriceps was conducted using a handheld dynamometer. Fifteen healthy, youth baseball pitchers (9.80 ± 1.08 years) threw a submaximal number of pitches and were tested before, immediately after, and for the next 4 consecutive days. Time in days required per muscle group to return to baseline force production levels were compared with Little League rest guidelines for pitchers. Results indicated that Little League rest requirements did not allow for sufficient recovery of lower extremity strength (p = 0.017). Results suggest that current Little League pitching guidelines provide an inadequate recovery period for youth pitchers, even when pitching a submaximal volume. Little League pitch count regulations and associated rest days may require revisions to avoid having youth athletes pitch while fatigued.